A Comparative Study of Institutionalized Orphans and Non-Orphan’s Use of Coping Strategies - Maryam Siddiqui, Amena Zehra Ali (Pakistan Journal of Psychology, 2018)
The study is aimed to comparatively analyze the use of coping strategies (i.e. adaptive and maladaptive) by children in orphanages in contrast to non-orphans. The sample of 209 children was recruited via purposive sampling, out of which 105 were children from different orphanages in Karachi whereas 104 children were living with their biological parents and were recruited from private schools of Karachi. Age of the children for both groups was 6-12 years. Adapted version of the Brief COPE (Siddiqui & Ali, in press) was used. Besides descriptive statistics, t-test was used to compare the means of both groups for each coping scale. Findings revealed that institutionalized orphans tend to rely more on maladaptive coping strategies, i.e. denial, behavioral disengagement, venting, acceptance (passive) and self-blame. Alternatively, non-orphans were found to use adaptive coping strategies (active coping, emotional support, instrumental support, positive reframing, planning and humor) more frequently than children from orphanage